Public Relations Communication Management of Pt. PLN (Persero) UID S2jb in the CSR Program "Light Up The Dream" as an Effort to Brand the Company - Aisyahtun Khairiah Sanida; Yenrizal; Putri Citra Hati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study discusses the communication management of Public Relations of PT PLN (Persero) UID S2JB in the Corporate Social Responsibility (CSR) Light Up The Dream program as a corporate branding effort . This program is present as a form of PLN's social concern for underprivileged people who do not have independent access to electricity. This research is motivated by the importance of effective communication management in the implementation of CSR programs in order to be able to build public understanding, minimize social misunderstandings, and strengthen the company's image in the eyes of the public. This research uses Communication Management Theory which emphasizes the process of planning, organizing, implementing, and controlling communication in achieving organizational goals. This study uses a qualitative descriptive method with a communication management approach. Data were obtained through observation, semi-structured interviews, and documentation. The research informants consisted of the Public Relations of PT PLN (Persero) UID S2JB and the community receiving assistance from the Light Up The Dream program. The data analysis technique uses thematic analysis through the process of grouping themes, interpreting data, and drawing conclusions. The results of the study show that Public Relations communication management is carried out through the stages of planning and implementing communication in a structured manner. Public Relations conducts internal coordination, preparation of communication messages, the use of digital media, mass media publications, and direct communication with the public and stakeholders. This program also implements two-way communication through interaction and response of the beneficiary community. In addition, there are several obstacles such as a lack of public understanding of the assistance mechanism and the potential for social jealousy. However, these obstacles are overcome through coordination with village officials, persuasive approaches, and more open publications. The Light Up The Dream program is considered to be able to strengthen the company's branding by forming a positive image of PLN as a company that cares about the underprivileged.